Educating future physicians for francophone official language minority communities in Canada: a case study - Schrewe, Brett; Yeuchyk, Tatiana; El Hafid, Melanie; Nyhof-Young, Joyce (Canadian Medical Education Journal, 2023)
Background: Over one million Francophone Canadians live in official language minority communities (OLMC) outside of Québec. Availability and accessibility of linguistically appropriate care to these OLMCs is lacking, resulting in poorer quality of care. To help address this health equity gap, the FrancoDoc program was created in 2015 to identify Francophone/Francophile medical students enrolled at medical faculties that use English as their primary language of instruction and equip them with skills to increase their medical French abilities. Little is known, however, about the affordances and limitations of this educational endeavour. Methods: Our qualitative instrumental single case study explored participants’ experiences with FrancoDoc, while also examining factors shaping the delivery of linguistically appropriate healthcare services to OLMCs. We conducted semi-structured interviews with medical students from across Canada and thematically analyzed these using a reflexive, inductive approach. Results: Four main themes were derived from 12 interviews: factors facilitating French language learning; barriers to French language learning; contextual factors shaping linguistically appropriate healthcare provision; and recommendations to improve healthcare education to better prepare learners to provide care to OLMCs. Conclusions: Medical student participants are highly motivated to engage in educational activities linked to FrancoDoc. Their efforts are nonetheless frequently impeded by barriers such as time constraints, irregular event programming, lack of regular clinical learning opportunities, and lukewarm support from faculties of medicine. If medical faculties are to realize their obligations to the OLMCs that they serve, recognition of language as a specific social determinant of health and more robust institutional supports for initiatives like FrancoDoc are paramount.